Synthesis and biological evaluation of cilengitide derivatives on TGF‐β1‐induced epithelial‐to‐mesenchymal transition in human non‐small cell lung cancer cells. Issue 6 (28th May 2022) - Park, Kyeong‐Yong; Jeong, Jisu; Kim, Jiyeon
Abstract: Epithelial‐to‐mesenchymal transition (EMT) is an important process leading to invasiveness of cancer cells and poor prognosis in non‐small cell lung cancer (NSCLC) progression. Cilengitide (cyclo[RGDf(NMe)V]), a cyclic RGD pentapeptide, has been shown to enhance the inhibitory effect of epidermal growth factor receptor (EGFR) inhibitors on TGF‐β1‐induced mesenchymal marker expression and invasion by NSCLC A549 cells. In this study, we synthesized cilengitide and derivatives and evaluated their biological effects on TGF‐β1‐induced EMT phenotype marker expression and invasion in human NSCLC cells. Among the synthesized derivatives, R‐1 (cRGDwV) and R‐7 (cRGDyV) were found to be the most effective in inhibiting the growth of NSCLC cells. These cilengitide derivatives showed an inhibitory effect on the TGF‐β1‐induced EMT process and invasion through inhibition of Smad or non‐Smad signaling pathways in NSCLC A549 cells. Through this study, we demonstrated that cilengitide derivatives containing the RGD sequence and hydrophobic amino acids, such as cilengitide, exhibit inhibitory effects on NSCLC cell growth and EMT inhibition. In addition, the potential of these peptides as a drug that can be used to inhibit metastasis of various cancers accompanying the EMT process was suggested. Abstract :